Effect of the sintering temperature on electrical properties of the Na0.54Bi0.46TiO2.96 compound. Issue 8 (15th April 2022) - Li, Minyan; He, Chan; Li, Xianyu; Wang, Weiguo; Liu, Ting; Wang, Xinfu; Wang, Dan; Hao, Gangling
Abstract: The Na0.54 Bi0.46 TiO2.96 compound was prepared by the sol-gel means and sintered at different temperatures. The effect of sintering temperature on the electrical properties and diffusion behavior of oxygen ions was systematically studied. The bulk conductivity of Na0.54 Bi0.46 TiO2.96 compound increases first and then decreases with the increase of sintering temperature. At the sintering temperature of 1273 K, the highest bulk conductivity of the Na0.54 Bi0.46 TiO2.96 sample can reach up to 3.35 × 10 -4  S/cm. The total conductivity of the Na0.54 Bi0.46 TiO2.96 sample shows a monotonous upward trend with increasing sintering temperature. The internal friction spectrum results present that the oxygen vacancy concentration and the relaxation activation energy of the Na0.54 Bi0.46 TiO2.96 sample show an upward trend, but the mobility of the oxygen vacancy diffusion decreases with the sintering temperature. The Na0.54 Bi0.46 TiO2.96 sample sintered at 1273 K is characterized by a higher oxygen vacancy concentration and mobility, resulting in the high grain conductivity.